Bleeding complications and antithrombotic treatment in 264 pregnancies in antiphospholipid syndrome. (September 2018) - Yelnik, C M; Lambert, M; Drumez, E; Le Guern, V; Bacri, J-L; Guerra, M M; Laskin, C A; Branch, D W; Sammaritano, L R; Morel, N; Guettrot-Imbert, G; Launay, D; et al.
Purpose: The purpose of this study was to evaluate the safety of antithrombotic treatments prescribed during pregnancy in patients with antiphospholipid syndrome (APS). Methods: This international, multicenter study included two cohorts of patients: a retrospective French cohort and a prospective US cohort (PROMISSE study). Inclusion criteria were (1) APS (Sydney criteria), (2) live pregnancy at 12 weeks of gestation (WG) with (3) follow-up data until six weeks post-partum. According to APS standard of care, patients were treated with aspirin and/or low-molecular weight heparin (LMWH) at prophylactic (pure obstetric APS) or therapeutic doses (history of thrombosis). Major bleeding was defined as abnormal blood loss during the pregnancy and/or post-partum period requiring intervention for hemostasis or transfusion, or during the peripartum period greater than 500 mL and/or requiring surgery or transfusion. Other bleeding events were classified as minor. Results: Two hundred and sixty-four pregnancies (87 prospectively collected) in 204 patients were included (46% with history of thrombosis, 23% with associated systemic lupus). During pregnancy, treatment included LMWH ( n = 253; 96%) or low-dose aspirin ( n = 223; 84%), and 215 (81%) patients received both therapies. The live birth rate was 89% and 82% in the retrospective and prospective cohorts, respectively. Adverse pregnancy outcomes occurred in 28% of the retrospective cohort and in 40% of the prospective cohort. No maternal death was observed in either cohort. A combined total of 45 hemorrhagic events (25%) occurred in the retrospective cohort, but major bleeding was reported in only six pregnancies (3%). Neither heparin nor aspirin alone nor combined therapy increased the risk of hemorrhage. We also did not observe an increased rate of bleeding in the case of a short interval between last LMWH (less than 24 hours) or aspirin (less than five days) doses and delivery. Only emergency Caesarean section was significantly associated with an increased risk of bleeding (odds ratio (OR) 5.03 (1.41–17.96); p =.016). In the prospective cohort, only one minor bleeding event was reported (vaginal bleeding). Conclusion: Our findings support the safety of antithrombotic therapy with aspirin and/or LMWH during pregnancy in high-risk women with APS, and highlight the need for better treatments to improve pregnancy outcomes in APS. PROMISSE Study ClinicalTrials.gov identifier: NCT00198068.